Design of financial statement preparation based on SAK EMKM using microsoft excel - Ifa Rosania Afif; Nawirah Nawirah (Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
Purpose - Micro, Small and Medium-sized Enterprises (MSMEs) are a pillar of the Indonesian economy, as evidenced by the ability of MSMEs to save the economy in Indonesia during the monetary crisis in 1998. There was a significant increase in the number of MSMEs in Indonesia, inseparable from the problems that caused the failure of MSME actors. Among the affecting factors are the simple management, lack of supervision of the production process and the quality caused by the system on the entity, the simple recording of financial statements, and limited market access. The purpose of this study is to facilitate the MSMEs XXX in preparing financial statements based on SAK EMKM using Microsoft Excel software.Method - This research uses a qualitative approach. The location of this research is MSMEs XXX which is located on Sunan Muria II Street No. 16 Malang. The data collection uses observation and interview techniques directly to researchers, the analytical method used is hermeneutics which means an approach to analyze and interpret data centered on the meaning of qualitative data.Result - The design of financial report preparation based on SAK EMKM using Microsoft Excel in MSMEs XXX includes income statement, financial position report, and notes on financial statements. The MSMEs found problems in preparing the financial statements because of the lack of adequate resources and supporting software.Implication - UMKM xxx is expected to be able compile financial statements based on SAK EMKM with microsoft excel software.Originality - This research is the first study at UMKM xxx by making financial reports based on SAK EMKM with microsoft excel software .